Empyema necessitans in a six-month-old girl. (3rd July 2019) - Goussard, P.; Gie, Robert; Janson, Jacques; Andronikou, Savvas
Abstract: Empyema necessitans is a rare complication of acute bacterial pneumonia, especially in children. It is a complication of empyema characterised by the extension of pus from the pleural cavity into the thoracic wall to form a mass of purulent fluid in the adjacent soft tissue. An inflammatory chest wall mass following pneumonia caused by Streptococcus pneumonia in a six-month-old infant is reported. The case emphasises that children presenting with persistent fever and a painful chest wall mass following pneumonia should be investigated immediately as there might be an urgent need for surgery.